2011
DOI: 10.1108/01435121111112907
|View full text |Cite
|
Sign up to set email alerts
|

Retaining academic librarians: by chance or by design?

Abstract: Purpose -This paper seeks to examine the direct and indirect strategies that academic libraries currently use to retain librarians and the levels of satisfaction librarians express about those strategies. Design/methodology/approach -The study consisted of a 23-item survey, administered online to current academic librarians. In total, 895 viable responses were received. Findings -Respondents reported that initiatives related to professional development are the most widely available type. Respondents expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…This is done through rewards for performing jobs effectively, building harmonious working relations between managers and employees and maintaining a healthy, safe work environment. Our review of the research literature indicated eight critical factors that must be considered in the retention of employees namely, employee commitment, compensation, job characteristics, training and development opportunities, career opportunities, supervisor support, work/life policies and turnover intention (Bhatnagar, 2007;Brundage & Koziel, 2010;Carraher et al, 2006;Chabault et al, 2012;Döckel, 2003;Flinkman et al, 2008;Gaiduk, Gaiduk, & Fields, 2009;Gberevbie, 2010;João & Coetzee, 2012;Kerr-Phillips & Thomas, 2009;Strothmann & Ohler, 2011;Tanton, 2007).…”
Section: Retention Factorsmentioning
confidence: 95%
See 1 more Smart Citation
“…This is done through rewards for performing jobs effectively, building harmonious working relations between managers and employees and maintaining a healthy, safe work environment. Our review of the research literature indicated eight critical factors that must be considered in the retention of employees namely, employee commitment, compensation, job characteristics, training and development opportunities, career opportunities, supervisor support, work/life policies and turnover intention (Bhatnagar, 2007;Brundage & Koziel, 2010;Carraher et al, 2006;Chabault et al, 2012;Döckel, 2003;Flinkman et al, 2008;Gaiduk, Gaiduk, & Fields, 2009;Gberevbie, 2010;João & Coetzee, 2012;Kerr-Phillips & Thomas, 2009;Strothmann & Ohler, 2011;Tanton, 2007).…”
Section: Retention Factorsmentioning
confidence: 95%
“…Research has suggested numerous reasons why employees consider leaving their employers, such as inadequate pay and benefits, lack of career opportunities, training and development, poor communication and subordinate-supervisor relationships, a negative perception of leadership and culture, an unsatisfactory work environment, a lack of autonomy and decision-making authority and conflict between family and work responsibilities (Carraher, Parnell, Carraher, Carraher, & Sullivan, 2006;Flinkman, Laine, Leino-Kilpi, Hasselhorn, & Salanterä, 2008;Gaiduk, Gaiduk, & Fields, 2009;Gberevbie, 2010;Strothmann & Ohler, 2011). Researchers recognize these reasons for leaving an organization as important factors to consider in retaining talented staff (Bhatnagar, 2007;Döckel, 2003;Döckel, Basson, & Coetzee, 2006;Kerr-Phillips & Thomas, 2009;Van Dyk, 2011).…”
mentioning
confidence: 98%
“…Job satisfaction and organizational commitment has received much attention in various organization industries including airways (Chen, 2006), educational institution (Gopinath, 2020;Anari, 2012, Wong & Tay, 2010Arif & Junaidah, 2011), library, (Noor & Noor, 2007;Strohmann & Ohler, 2011), health (Puriene, Petrauskiene, Janulyte, & Balciuniene, 2007), tourism (Gunlu et al, 2011), police (Abdulla, Djebarni, & Mellahi, 2011) and others. With regard to the importance of satisfying and retaining employees, most organizations are now being highly concern to be proactive in understanding and dealing with these issues.…”
Section: Job Satisfaction and Organizational Commitmentmentioning
confidence: 99%
“…While there are libraries actively engaged in strategically integrated internal knowledge management processes (Balagué et al, 2015(Balagué et al, , 2016, it is clear that most libraries have not adopted such processes. Relatively recent studies indicate that, at least in academic libraries, there is an overall lack of attention to retention in general (Strothmann and Ohler, 2011) and to specific programs that might aid in retention (Harrington and Marshall, 2014). Without CLO-like oversight of retention initiatives, libraries will continue to face the challenges associated with engaging and retaining employees common to all organizations including libraries (Markgren et al, 2007;Deloitte, 2016).…”
Section: Retentionmentioning
confidence: 99%